Whisker-mediated transformation of peanut with chitinase gene enhances resistance to leaf spot disease - Hassan,Mahmood ul (2016)
Abstract Peanut (Arachis hypogaea) is an important legume and oilseed crop, native to South America and grown in all tropical and temperate regions of the world. A simplified and rapid direct gene delivery system in peanut was developed by vortexing silicon carbide whiskers with callus and with plasmid harboring chitinase and hygromcin genes. The effects of callus age and whisker quantity on transformation efficiency were evaluated. Transformation efficiency (6.88%) was highest when 200 mg of whiskers were used with 5 µg plasmid for 2 g of 20-day-old callus. Hygromcin-resistant calli were regenerated to complete plants which produced seeds normally. Transgene insertion and number of transgene copieswere confirmed by PCR and southern blot analyses, respectively. Transgene expression was evaluated by a pathogenecity test and RT-PCR analysis. In transgenic events, the resistance level to leaf spot disease was far higher than in control plants.